Effects of Coenzyme Q10 Supplementation on Serum Adiponectin Levels: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Nazary-Vannani, Ali; Ghaedi, Ehsan; Salamat, Shekoufeh; Sayyaf, Afsaneh; Varkaneh, Hamed K.; Mohammadi, Hamed; Djalali, Mahmoud (Current Drug Therapy, 2020)
Background: Adiponectin, a well-known adipokine plays a number of regulatory actions in human body metabolism. Decreased levels of adiponectin have been reported in type 2 diabetes mellitus, cardiovascular diseases, metabolic syndrome and hypertension. Coenzyme Q10 (Co Q10) is a fat-soluble antioxidant substance which has been reported to be effective in several metabolic disturbances such as insulin resistance and inflammation. Objective: Present systematic review and meta-analysis were performed to assess the effects of CoQ10 supplementation on adiponectin serum level. Methods: A comprehensive search was performed in electronic databases including EMBASE, Google scholar, and PubMed up to January 2018. A meta-analysis of eligible studies was performed using random effects model to estimate pooled effect size of CoQ10 supplementation on adiponectin. Results: A total of 209 subjects were recruited from 5 eligible studies. Meta-analysis did not suggest any significant effect of CoQ10 supplementation on adiponectin serum level (0.240 mg/dl, 95%CI: -0.216, 0.696, P= 0.303), without significant heterogeneity between included studies (I2= 40.9%, p= 0.149). Conclusion: Although present meta-analysis did not indicate any significant effects of CoQ10 supplementation on serum adiponectin levels but future long-term dose-response trials are needed before any firm conclusion.
Keywords: diabetes mellitus